2003
DOI: 10.2176/nmc.43.188
|View full text |Cite
|
Sign up to set email alerts
|

Acute Surgery for Ruptured Dissecting Aneurysm of the M3 Portion of the Middle Cerebral Arteryda-Case Report-

Abstract: A 65-year-old woman presented with a ruptured dissecting aneurysm of the M 3 portion of the middle cerebral artery (MCA) manifesting as disturbance of consciousness and motor aphasia. Computed tomography revealed subarachnoid hemorrhage. Emergent angiography demonstrated segmental aneurysmal dilatation of the M 3 portion of the left MCA. Infectious aneurysm was excluded. Surgery was performed to prevent repeated hemorrhage from the aneurysm. The lesion was excised and flow to the distal MCA was preserved with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 16 publications
0
23
0
1
Order By: Relevance
“…Microneurosurgical clipping and trapping with excision of aneurysm are the treatment options available. [14] In our case aneurysm was trapped and excised. Horiuchi et al reported about postsurgery recuperation that despite the poor pre-operative grades due to ICH early surgery gained favorable outcome, while Rinne, et al reported that unfavorable outcome was achieved due to ICH.…”
Section: Discussionmentioning
confidence: 58%
“…Microneurosurgical clipping and trapping with excision of aneurysm are the treatment options available. [14] In our case aneurysm was trapped and excised. Horiuchi et al reported about postsurgery recuperation that despite the poor pre-operative grades due to ICH early surgery gained favorable outcome, while Rinne, et al reported that unfavorable outcome was achieved due to ICH.…”
Section: Discussionmentioning
confidence: 58%
“…[1][2][3]5,6,8,9,11,14,[17][18][19][20] Study of the mechanisms of ruptured/unruptured arterial dissection using immunohistochemical findings of lysyl oxidase (Lox) and matrix metalloproteinases (MMPs) in multiple dissecting aneurysms demonstrated that Lox1, MMP-2, and MMP-9 were remarkably expressed in hypertrophic media outside the intima in ruptured dissecting aneurysms, but were expressed in the intima and inside hypertrophic media in unruptured dissecting aneurysms. 17) Our patient was hospitalized with ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…On the Basal Diamox other hand, distal MCA aneurysms, especially dissecting aneurysms are rare. There are just four reported cases of spontaneous dissecting aneurysms of the M3 segment or more distal locations 4) , and only one case of saccular aneurysm has been reported in the literature 1) . However, most of these cases were ruptured aneurysms, and the patients had no other vascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The routine surgical treatment for dissecting aneurysms of the main trunk of MCA is bleb clipping and wrapping in order to preserve the perforating artery, while that for distal part aneurysms, such as those located in the M2 or M3 segments, is resection, trapping or proximal ligation and STA-MCA anastomosis, if possible, in order to maintain MCA flow distal to the lesion 4) . Our patient had distal M4 aneurysm associated with ipsilateral ICA occlusion, and a Diamox-SPECT scan showed moderately decreased perfusion/reserve capacity in the right MCA territory, indicating that he needed an additional supply of blood flow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation